Diversity and Community Structure of Soil Nematodes Associated with Tuberose (Polianthes tuberosa L.) from District Hapur (Uttar Pradesh) (Indian Journal of Nematology, 2019)
Study was undertaken to explore diversity and community structure of soil nematodes associated with Tuberose in 2018. During the survey, collected 68 soil samples from different localities of five villages in each of Hapur, Garhmukteshwar and Dhaulana thesil of district Hapur (Uttar Pradesh). Different nematode genera and trophic groups were assessed in terms of absolute frequency, relative frequency, density, relative density, prominence value and relative prominence value. The analysis revealed the association of the nematode genera, among which eight belong to plant parasitic nematodes; five belong to predaceous nematodes and four to bacteriovorus nematodes. Results showed that Pratylenchus sp. was more frequent, while Meloidogyne incognita was the most abundant and prominent nematode in the community. All the predatory and bacteriovorus nematodes found are the reports first time from this crop as well as regions. This study indicated that a great diversity of nematode fauna are still unexplored and there is an urgent need to explore diversity of both beneficial as well as harmful nematodes in tuberose ecosystem.